Scavengers As an Alternative Waste Management Project: a Study On The Civil Society of Kiringan Village in Sustainable Development Goals 15 through 3R Waste Management - Saputra, Hendra Lana; Noormansyah, Reza (Universitas Widya Mataram, 2024)
This research aims to determine the role of scavengers in Kiringan Village, Magelang City, within the framework of civil society concerning their livelihoods, namely managing and recycling waste, which contributes to Sustainable Development Goals (SDGs) 15. Waste itself has become a national problem, with the volume of garbage reaching 35,000. Ninety-three million tons in 2022 can be broken down further, with Central Java Province coming at 5.76 million tons and Magelang City at 80.51 tons per day. This condition becomes problematic amidst demands regarding the universal norm SDG 15, namely